Quarter-turn valves : head loss, torque, and cavitation analysis - Bosserman, Bayard E., II; Holstrom, John R. (American Water Works Association, 2017)
Recommended methods for calculating operating torque, head loss, and cavitation for quarter-turn valves typically used in water works service. M49 also provides guidance on generally available methods for using quarter-turn valves as well as their cavitation, flow, and torque characteristics.
Keywords: Water-pipes -- Valves.; elektronické knihy; electronic books